Türkiye Gazetesinin gelişimi ve Türk medyasındaki yeri - Selek, Fatih (My University, 2025)
Bu çalışma, 1970 yılında Enver Ören tarafından Hakikat ismiyle İstanbul'da kurulan Türkiye gazetesinin tarihini incelemektedir. Gazetenin hangi kadro ile hangi şartlarda kurulduğu, yayın hayatı boyunca nasıl bir politika benimsediği, Türk siyasi tarihinin kırılma noktalarında nasıl tavır takındığı, sahiplik yapısı, yönetim ve yazar kadrosu, promosyonları, yan kuruluşları ve basın sektörüne getirdiği yenilikler birincil kaynaklardan anlatılmıştır. Gazete, siyasi ve teknik olarak ayrı ayrı incelenmemiş, evreler bütüncül bir bakış açısıyla kronolojik olarak ele alınmıştır. Çalışma üç bölüme ayrılmıştır. Birinci bölümde, Türkiye’de yazılı gazeteciliğin gelişimi incelenmiştir. İkinci bölümde Türkiye gazetesinin gelişim süreci anlatılmaya çalışılmıştır. İsim değişikliğini de içine alan 1970-1980 yılları, kuruluş dönemi olarak değerlendirilmiştir. Bu dönemde teknik olarak büyük bir değişiklik olmadığı için daha çok yayın politikasına odaklanılmıştır. 12 Mart 1971 muhtırasına, fikri kavgalara, sahiplik yapısının değişimine, 1974 Kıbrıs Barış Harekâtına ve sokak çatışmalarına Türkiye gazetesinin nasıl baktığı manşet ve baş yazı okumaları üzerinden irdelenmiştir. Turgut Özal ile birlikte ekonomik programın değiştirdiği 1980 darbesi sonrası gelişme ve büyüme dönemi olarak ele alınmıştır. Gazetenin elden dağıtım sistemini hayata geçirmesi, yan yayınları, hamleleri, basın dışı ticari faaliyetleri, tiraj rekoru kırması, kendi matbaasını kurması, 60 şirketli bir holdinge dönüşmesi, televizyon ve haber ajansını kurması, 1994 ekonomik krizin ile 28 Şubat siyasi krizinden nasıl etkilendiği bu dönemde anlatılmıştır. 2001 ekonomik krizi Türkiye gazetesinin bağlı olduğu İhlas Holding’i olumsuz etkilemiş, gazete ve kardeş kuruluşları küçülmeye gitmiştir. 2000-2010 yılları arası, durgunluk ve toparlanma dönemi olarak değerlendirilmiştir. AK Partili yıllar, Enver Ören’in vefatı, logo değişikliği, Gezi olayları ve 15 Temmuz gibi kırılma dönemleri 2010 sonrasının başlıkları arasında irdelenmiştir. Son bölümde ise gazetenin yönetimi, genel yayın müdürleri, yazı işleri müdürleri, tirajı ele alınmıştır.

This study examines the history of the Türkiye newspaper, founded in Istanbul in 1970 by Enver Ören under the name Hakikat. It details the team and conditions of its establishment, the policies it adopted throughout its publication history, its stances during pivotal moments in Turkish political history, its ownership structure, management and writing staff, promotions, subsidiary organizations, and innovations brought to the press sector, all based on primary sources. The newspaper has not been analyzed separately in political and technical terms; instead, its phases are addressed chronologically with a holistic perspective.The study is divided into three sections. The first section explores the development of print journalism in Türkiye. The second section narrates the development process of the Türkiye newspaper. The years 1970–1980, including the name change, are considered the founding period. As there were no significant technical changes during this period, the focus is primarily on the publication policy. The newspaper’s perspective on the March 12, 1971 memorandum, ideological conflicts, changes in ownership structure, the 1974 Cyprus Peace Operation, and street clashes is analyzed through readings of headlines and editorials. The period following the 1980 coup, shaped by Turgut Özal’s economic program, is addressed as a phase of development and growth. This era covers the newspaper’s implementation of a hand-delivery distribution system, its side publications, strategic moves, non-press commercial activities, record-breaking circulation, establishment of its own printing press, transformation into a holding company with 60 subsidiaries, founding of a television channel and a news agency, and the impacts of the 1994 economic crisis and the February 28 political crisis.The 2001 economic crisis adversely affected İhlas Holding, to which the Türkiye newspaper is affiliated, leading to downsizing for the newspaper and its sister organizations. The years 2000–2010 are evaluated as a period of stagnation and recovery. The AK Party era, Enver Ören’s passing, logo change, the Gezi protests, and the July 15 coup attempt are among the key events examined for the period after 2010. The final section addresses the newspaper’s management, editors-in-chief, newsroom directors, and circulation. newspaper, İhlas Media, Enver Ören, TGRT,
Keywords: Enver Ören; Enver Ören Gazetecilik; Gazetecilik; History; İHA; İhlas Media; İhlas Medya; Journalism; Tarih; TGRT; Turkey; Turkish newspapers; Türk gazeteleri; Türkiye; Türkiye Gazetesi; Türkiye Nespaper